Role of Mass Media in Promoting Environmental Health and Awareness in Bangladesh: A Case Study - Shumshunnahar, Mst.; Amin, Md Ruhul (Advances in Social Sciences Research Journal, 2023)
The general public, local producers, scientists, policymakers, administrators, and government politicians all play important roles in the development and dissemination of awareness. In the context of the environment and development paradox, environmental awakening in developing nations such as Bangladesh is a current topic. Environmental awareness assists in acquainting social groups and individuals with the environment and associated issues. As the general population of Bangladesh explores information about nature, environment, and biodiversity through television, newspapers, and radio, mass media can play a crucial role in enhancing the public's knowledge of environmental challenges, issues, eco-friendly technologies, laws, and policies, as well as development-related environmental issues.